(untitled) (Società e diritti, 2017)
Aim of the contribution is to offer a quick overview on the principle of effectiveness, with a focus on doctrinal positions of Catelani A. and H. Kelsen, but also to identify possible applications of the principle of effectiveness, in a new sematic perspective of internal public law. Key words: Legal-positivism, natural law, human rights